Revisiting persuasion in oral academic and professional genres: Towards a methodological framework for Multimodal Discourse Analysis of research dissemination talks - Julia Valeiras-Jurado; Noelia Ruiz-Madrid; Geert Jacobs (Ibérica, 2018)
Previous work on oral genres (Kress & Van Leeuwen, 2001; Kress, 2010; Bateman, 2011) as well as on persuasion (O’Keefe, 2002; Perloff, 2003; Poggi & Pelachaud, 2008) has indicated that effective persuasive oral communication depends heavily on the use of a wide range of different semiotic modes including words, gestures and intonation. However, little attention has been paid so far to how speakers convey their communicative intentions orchestrating different modes into a coherent multimodal ensemble (Kress, 2010). In this paper we propose a methodological framework for Multimodal Discourse Analysis (MDA) of persuasion in oral academic and professional genres. Drawing on previous studies on persuasion (Fuertes-Olivera et al., 2001; O’Keefe, 2002; Perloff, 2003; Virtanen & Halmari, 2005; Dafouz-Milne, 2008), our framework combines earlier proposals for MDA (Querol-Julián, 2011; Querol-Julián & Fortanet-Gómez, 2014) with an ethnographic perspective (Rubin & Rubin, 1995). Our study focuses specifically on the analysis of persuasive strategies used in dissemination talks. The proposed MDA caters for the following modes: words, intonation, head movements and gestures. Preliminary findings hint at a relation between persuasion and so-called modal density (Norris, 2004). Finally, we propose a tentative taxonomy of persuasive strategies and how they are realised multimodally.